THE EFFECT OF BUDGET REFOCUSING DURING THE COVID-19 PANDEMIC ON THE REALIZATION OF THE APBD IN CENTRAL JAVA PROVINCE - Aerona Khatulistiwa (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2021)
At the beginning of March 2020 there was a Covid-19 pandemic that hit Indonesia which eventually gave rise to several social restrictions policies for the community. In this case, several financial sectors are affected by the policy. In the context of handling the Covid-19 pandemic, there must be a budget refocusing or reallocation focused on handling Covid-19 in Indonesia. However, the refocusing effort that has been carried out in a short time has resulted in problems that have an impact on the realization of the reallocated budget (before the pandemic). In this regard, a government regulation policy in lieu of the Law is formed and issued which is the basis for the replacement of the Law on Regional Government. In this study, the researcher uses a qualitative descriptive method, which is a non-quantitative data collection and analysis method with the aim of exploring social relationships and a description of the reality experienced by the response, or what is commonly referred to as the problem formulation to be used to explore in depth research. The locus of this research is in Central Java Province, using secondary data sourced from several literature studies.